Parotid oncocytoma: diagnostic vs surgical dilemma - Thapa, Suman; Parajuli, R.; Limbu, T.; Bhandari, R. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Oncocytomas are rare benign tumors of salivary gland origin, most often seen involving the parotid gland. They should be considered as a possible diagnosis in elderly patients with slow growing, nontender and mobile parotid swelling. We report here a middle aged female with left parotid swelling that was misdiagnosed on fine needle aspiration cytology and confirmed with histopathology report. Rarity of the disease with frequent cytologic overlaps and interpreter’s inexperience account for the majority of aspiration cytology pitfalls. Therefore, aspiration cytology alone may be misguiding at times, leading to surgical over-correction and further potential complications. The ever-changing trends of mucoepidermoid carcinoma (pre-operative, fine needle aspiration cytology), pleomorphic adenoma (intraoperative) and oncocytoma (post-operative, histopathology) have created diagnostic dilemma, confusion and challenged the surgical rationale. In cases with discrepancy between clinical, cytological and pathological reports, diagnostic as well as surgical dilemma exists wherein a thorough diagnostic re-assessment and a proper surgical revision is warranted.